Integral Factor Assessment of Formation and Development of Finno-Ugric Tourist Cluster - MAYKOVA, Svetlana E.; OKUNEV, Denis V.; GVOZDETSKAYA, Irina V. (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).01, 2017)
In the article, we discuss the possibility of creating of Finno-Ugric tourist cluster in Russia on the territory of the Mari El Republic. This cluster allows us to use all resources of enterprises and organizations more efficiently that are involved in the production process of tourist and recreational services and enhance their quality and, therefore, competitiveness in external and internal markets in services. The factor analysis allowed us to identify factors that affect the formation of tourist cluster. The research, using the methods of SNW-analysis and integral assessment of the degree of factor influence on tourism sector and hospitality, allowed us to determine the opportunities and prospects of different types and directions of tourism in Finno-Ugric tourist cluster. We created the map of strategic development of tourist clusters in the region, which is based on analysis of tendencies and dynamics of development of tourist market in the Mari El Republic and the extent and nature of influence of external and internal factors on the formation of the hospitality industry. The map represents the ranking of developing prospects of separate kinds of tourism in Finno-Ugric tourist cluster due to the available natural resources, geographical location, environmental well-being, well-preserved nature and traditional culture of the local population.